A Study of the Effect of Zinc Organic Metal Composite Layers on the Frequency of Quartz Crystal Sensor - Fifin Tresna Juwita; Fadli Robiandi (LPPM ITK, 2021)
The performance, sensitivity, and corrosion protection on the QCM sensor requirement be improved to maximize the value. Therefore, the functional material coating was carried out. The addition of the polystyrene and ZnPc deposited using the vacuum evaporation method. This study intends to the morphology structure and effect of the coating, to improve performance through the annealing process based on the impedance value at QCM. The frequency measurement before and after the coating process was carried out with a variation of the deposition time, which is 1 minute 30 seconds, 1 minute 45 second, 2 minutes, 2 minute 20 seconds, and 4 minutes. The coating and annealing resulted from the surface structure of the QCM sensor are smooth, small porous, and homogeneous. In addition, the impedance to frequency graph indicates a low damping effect means the QCM sensor does not respond viscoelasticity.